Analogy and Reanalysis in Indonesian Grammatical Change: A Morphological and Syntactic Study - Saiyidinal Firdaus (Journal of Language, Literature and Teaching, 2026)
This study examines the interaction of reanalysis and analogy in Indonesian grammatical change from a combined morphological and syntactic perspective. Although both mechanisms are central to historical linguistics, researchers often treat their relationship descriptively rather than empirically and rarely use a unified analytical framework, particularly for non-Indo-European languages. Addressing this gap, the study aims to provide a mechanism-oriented account of how grammatical change emerges and becomes systemically integrated in Indonesian. The study employs a corpus-based qualitative–quantitative design, drawing on naturally occurring data from multiple written registers. Analysis integrates morphological diagnostics, syntactic distribution, and frequency-based evidence to identify patterns of change. Reanalysis is inferred from shifts in structural interpretation, including changes in argument structure and constructional alignment, while analogy is examined through patterns of distributional extension and frequency-sensitive generalization across related constructions. The findings demonstrate that reanalysis functions as the initial trigger of change by restructuring morphosyntactic relations but does not by itself ensure productivity. Instead, only those reanalyzed patterns that align with high-frequency and highly schematic constructions undergo analogical extension and become stabilized. This selective diffusion results in the formation of novel constructional patterns and facilitates the reorganization of the grammatical system. The study argues that Indonesian grammatical change is best explained as constructional network restructuring resulting from the interaction of reanalysis and analogy. By offering an empirically grounded and theoretically explicit model, this research contributes to a more typologically inclusive understanding of grammatical change and provides a replicable framework for integrating morphological, syntactic, and usage-based approaches in diachronic studies.